2021
DOI: 10.1016/j.amsu.2021.102236
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mode of delivery, maternal age, birth weight, gender and family history on screening hearing results: A cross sectional study

Abstract: Introduction Congenital hearing impairment is one of the principal issues that make distress to families especially those with a family history of hearing problems. Early detection of hearing impairment can make a difference regarding cognitive, attention, learning, speech, and social and emotional development of babies. Otoacoustic test emission is a very common screening test that can be used to pick up early cases and relieve family stress. We tried to evaluate the factors that may disrupt our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…The high test failure rate may be due to the short hospital stay of the mothers and, accordingly, the early testing after delivery (10). On the other hand, Al-Balas et al reported higher failure rates with VD, and Güven reported no difference between the groups (17,18). In our study, we observed no difference between the CS group and the VD group regarding hearing screening results.…”
Section: Discussioncontrasting
confidence: 51%
“…The high test failure rate may be due to the short hospital stay of the mothers and, accordingly, the early testing after delivery (10). On the other hand, Al-Balas et al reported higher failure rates with VD, and Güven reported no difference between the groups (17,18). In our study, we observed no difference between the CS group and the VD group regarding hearing screening results.…”
Section: Discussioncontrasting
confidence: 51%
“…In the 2021, The study of Al-Balas, a statistically significant relationship was found between family history and the results referred to the first OAE. According to Shahid in (Al-Balas, 2021) also reported that the probability of an OAE referral in infants with a family history of deafness is 11 times higher than the probability of infants without a family history [24]. The use of ototoxic drugs in this study could not be analyzed because it was found that most of the mothers did not exist and did not know that they had used ototoxic drugs during pregnancy.…”
Section: Discussionmentioning
confidence: 81%
“…1368 neonates (96.8%) passed the first OAE (otoacoustic emissions) in both ears in Al-Balas et al (7) research, whereas 45 babies (30 females and 15 males) failed the first OAE in one or both ears at a rate of 3.2 percent. The lack of failed OAE in this study is attributed to the limited number of cases and short duration of the study.…”
Section: Discussionmentioning
confidence: 92%